IDENTIFIKASI MISKONSEPSI SISWA PADA MATERI SISTEM REPRODUKSI - Yusi Ardiyanti; Marsah Rahmawati Utami (Program Studi Pendidikan Biologi, FKIP Unpas,, 2018)
Understanding the concept of biology is necessary in the integration of nature and technology in everyday life, if the concept of understanding is strong, students can develop and understand higher concepts. But sometimes students have a different understanding of concepts with scientifically accepted concepts and that will lead to misconceptions. The purpose of this study is to determine whether there is misconception in students and sub-concept what most misconception in reproduction system material. To calculate the misconception level of the Certainty of Response Index (CRI) method with the subjects of the study were students of class XI SMA 2 Cikampek. The data can show students misconception for some sub-concepts. The highest misconceptions exist in the menstrual subconses, which is 32.5% while the lowest is in the 10% gamete formation subconsep. This is because students interpret their own understanding of a material based on a text book that is read and an explanation from the teacher.